2018
DOI: 10.1128/msphere.00023-18
|View full text |Cite
|
Sign up to set email alerts
|

A Predicted Mannoprotein Participates in Cryptococcus gattii Capsular Structure

Abstract: Cryptococcus gattii has the ability to escape from the host’s immune system through poorly understood mechanisms and can lead to the death of healthy individuals. The role of mannoproteins in C. gattii pathogenicity is not completely understood. The present work characterized a protein, Kpr1, that is essential for the maintenance of C. gattii main virulence factor, the polysaccharide capsule. Our data contribute to the understanding of the role of Kpr1 in capsule structuring, mainly by modulating the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The fungal cell wall made up of α and β glucans, chitin, chitosan, and mannoproteins, is vital for fungal growth and development and is also one of the most significant drug development targets [36,37]. The results of previous studies showed that mannoproteins play a vital role in fungal virulence or cell wall integrity, such as Cig1 in C. neoformans, Krp1 in C. gattii, and Mp1p in T. marneffei [21,22,26]. Given mannoproteins' role in fungal virulence or cell wall integrity in fungal pathogens, it might be one of the potential targets for antifungal drug development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal cell wall made up of α and β glucans, chitin, chitosan, and mannoproteins, is vital for fungal growth and development and is also one of the most significant drug development targets [36,37]. The results of previous studies showed that mannoproteins play a vital role in fungal virulence or cell wall integrity, such as Cig1 in C. neoformans, Krp1 in C. gattii, and Mp1p in T. marneffei [21,22,26]. Given mannoproteins' role in fungal virulence or cell wall integrity in fungal pathogens, it might be one of the potential targets for antifungal drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Cadieux et al showed that the C. neoformans mannoprotein Cig1 helps get iron from heme and further proved that the Cig1 and the ferroxidase Cfo1 jointly regulate the virulence of C. neoformans [21]. Reuwsaat et al found that the predicted mannoprotein Krp1 is required for the cell wall structural integrity but is not necessary for fungal virulence in vivo in C. gattii [22]. Viudes et al found that Candida albicans surface mannoprotein MP58 could elicit a strong antibody response during infection.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, cells were fixed in 4% paraformaldehyde and washed three times with PBS. C. neoformans cells were placed on glass slides and mixed with similar volumes of India ink, and the capsule was measured as previously described ( 104 ).…”
Section: Methodsmentioning
confidence: 99%
“…As well as common pathogenic fungi, cryptococcal cells express highly mannosylated proteins, referred to as mannoproteins (MPs), on the cell surface and can secrete them to the extracellular space during infection. 47,48) Cryptococcal cells require MPs for infection to progress and therefore MPs are feasible targets for vaccine antigens. In contrast to CPs, MPs are T-cell dependent (TD) antigens, and vaccines containing cryptococcal MPs likely induce CMI and AMI for protection against cryptococcosis.…”
Section: Mannoproteinsmentioning
confidence: 99%